THE STUDENTS’ PERCEPTION OF THE ONLINE MEDIA USED BY TEACHER IN LEARNING ENGLISH - Aprilia Prabawati; St. Asriati AM; St. Asmayanti AM (FKIP Unismuh Makassar, 2021)
Research about online media was carried out during a pandemic era, online media can make easier for teacher to teach even without face to face. This research aimed to find out (1) The kinds of online media used by the teacher in learning English; (2) The students' perception of the online media used by the teacher in learning English. This used a Qualitative research; the instrument was an interview. The interview was distributed to the students that consisted of 20 students of the eleventh grade students at SMA Negeri 9 Gowa. The findings of the research showed the kinds of the online media used by teacher when learning english were Google classroom, Youtube, Google form and WhatsApp (WA). The researcher also gave some positive perception toward the online media used by teacher in learning english that is : The media help students to understand about the lesson easily and add insight and references, Increase students’ motivation and interest in the learning, learning is more interesting, fun, relaxed and not boring, prevend and decide the spread of Covid-19 and effective, efficiend and saving time.